PROTECTION FOR REGISTERED TRADEMARK UNDER INDONESIAN LAW AND THE WTO AGREEMENT ON TRADE-RELATED ASPECTS OF INTELLECTUAL PROPERTY RIGHTS (TRIPS) - Nabila, Diah Damba; Sanusi, Sanusi (Student Journal of International Law, 2023)
This study examines the legal protections available to registered trademarks, specifically focusing on trademark violations with reference to the Warkop DKI and Warkopi cases. The normative method is employed to explore the normative issues surrounding registered trademarks. The findings indicate that the legal protection of trademarks in Indonesia follows a repressive approach that aligns with the provisions of the TRIPS Agreement. In Indonesia, trademarks receive protection after being registered under the Indonesian Trademark Law of 2016. The trademark disputes between Warkop DKI and Warkopi exemplify instances of registered trademark infringement, along with other similar cases that serve as comparative legal references. The provisions of the law and the TRIPS Agreement do not condone violations of registered trademarks. Therefore, through the repressive protection framework adopted by Indonesia, Warkop DKI can pursue legal action to address trademark issues. It is crucial to establish clarity in differentiating trademarks and improve practices to prevent similarities among registered trademarks. This responsibility lies with the relevant trademark agencies, which should evaluate and respond to trademark disputes. In any trademark dispute, the involved parties must be able to comprehend and articulate the nature of the dispute that has arisen.